Changes in social function and body image in women diagnosed with breast cancer undergoing chemotherapy - Sabrina Nunes Garcia; Raquel de Castro Figueiredo Pereira Coelho; Pamella Naiana Dias dos Santos; Mariluci Alves Maftum; Maria de Fátima Mantovani; Luciana Puchalski Kalike (Universidade Estadual de Maringá, 2017)
The objective of this study was to investigate the impairment of social and emotional functions, body image and future perspective in women with breast cancer undergoing chemotherapeutic treatment. This is a longitudinal research conducted from October 2012 to October 2013 at the chemotherapy unit of a private institution of Oncology located in Curitiba, PR, Brazil. Sociodemographic and clinical questionnaires were applied, Quality of Life Questionnaire Core 30 e Quality of Life Questionnaire - Breast Cancer Module, to 48 women subjected for the first time to chemotherapy, in three different stages of the treatment. Analysis with Friedman`s, Spearman and Kruskal-Wallis nonparametric tests was performed. Changes were observed in social function and body image, which compromised quality of life significantly. Results can subsidize the planning of and adjustments to the care provided to these women by considering the perception about the impact of therapy on QL and their perspectives.